ODOL POLICY AS A LOCAL POLITICAL ISSUE: EXAMINING THE PALEMBANG CITY GOVERNMENT’S RESPONSE TO PUBLIC PRESSURE - Ibrahim Mifthafariz Mirza; Najmi Muhammad Fadli (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This study examines the political dynamics underlying the implementation of the Over Dimension and Overload (ODOL) policy in Palembang City, Indonesia. Using a qualitative-descriptive approach supported by official transportation data, accident statistics, and media analysis, the research explores how public pressure influences local government responsiveness toward ODOL enforcement. Findings reveal that weak implementation stems not only from institutional limitations but also from political compromises between local authorities and economic actors. The growing number of accidents and fatalities has intensified public scrutiny, transforming ODOL from a technical issue into a politically charged policy arena. The study demonstrates that public pressure serves as a catalyst for symbolic yet visible governmental action, while long-term effectiveness requires digital monitoring innovation, cross-agency collaboration, and participatory accountability. This research contributes to understanding how local political responsiveness shapes policy outcomes in developing democracies, particularly within decentralized governance systems.